Do high housing prices crowd out young professionals?—micro-evidence from China - Yemin, Ding; Lee, Chin; Mengqiu, Lu; Peidong, Deng (Taylor and Francis Group, 2022)
Motivated by the growing trend of young professionals flowing out of high-profile cities in China, this study examines whether high housing prices have a crowding-out effect on young professionals across 235 Chinese cities. Using a conditional logit model with multiple control variables related to the economy, the social environment, and city location, the results showed an inverted U-shaped relationship between a city’s house prices and young professionals’ potential migration into the city. We also performed a series of robustness checks and categorised the sample by gender, academic qualification, and marital status. The results indicated the same inverted U-shaped relationship, but with different extreme points for house prices across the sub-samples. The findings offer suggestions for Chinese local governments to attract young professionals by regulating housing prices in cities where prices surpass the extreme point.